2015
DOI: 10.14791/btrt.2015.3.2.132
|View full text |Cite
|
Sign up to set email alerts
|

Remote Postoperative Epidural Hematoma after Brain Tumor Surgery

Abstract: A postoperative epidural hematoma (EDH) is a serious and embarrassing complication, which usually occurs at the site of operation after intracranial surgery. However, remote EDH is relatively rare. We report three cases of remote EDH after brain tumor surgery. All three cases seemed to have different causes of remote postoperative EDH; however, all patients were managed promptly and showed excellent outcomes. Although the exact mechanism of remote postoperative EDH is unknown, surgeons should be cautious of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…The mean age of patients who developed remote postoperative EDH was 41 years with all 3 patients in our study being less than 50 years. Similar results have been published by Chung et al 4 All 3 of their patients were less than 30 years and in their extensive review of literature, authors found only 1 patient of more than 50 years who had developed remote postoperative EDH. Similar findings have been reported by other authors 5 and it is safe to state that this entity is mainly seen in young and middle age group.…”
Section: Discussionsupporting
confidence: 86%
“…The mean age of patients who developed remote postoperative EDH was 41 years with all 3 patients in our study being less than 50 years. Similar results have been published by Chung et al 4 All 3 of their patients were less than 30 years and in their extensive review of literature, authors found only 1 patient of more than 50 years who had developed remote postoperative EDH. Similar findings have been reported by other authors 5 and it is safe to state that this entity is mainly seen in young and middle age group.…”
Section: Discussionsupporting
confidence: 86%
“…This hypothesis was supported by a 1986 study by Fukamachi et al, who statistically analyzed 1105 cases involving craniotomy and found that remote epidural hematoma mainly occurred in patients with hydrocephalus and/or aneurysm [ 6 ]. Recently, in 2015, Chung et al reported three cases of remote epidural hematoma after brain tumor surgery, none of which involved meningioma; therefore, this type of remote hemorrhage appears to be independent of brain tumor type [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…It can occur either at the site of EVD placement or at a distant site. [ 1 ] In our case, hematoma occurred remotely at the parietal lobe on the opposite side.…”
Section: Discussionmentioning
confidence: 59%